First online field measurements of chlorothalonil volatilisation using proton transfer mass spectrometry and inverse modelling - Benjamin Loubet; Carole Bedos; Julien Kammer; Céline Decuq; Florence Lafouge; Baptiste Esnault; Raluca Ciuraru; Sandy Bsaibes; Pauline Buysse; Enrique Barriuso; Maria Raffaella Vuolo; Valérie Gros (Scientific Reports)
Abstract Pesticide usage has been expanding since the 1950s. Their use has affected human and environmental health negatively for decades. Recent studies have shown that gaseous pesticide diffusion in the atmosphere, known as volatilisation, may contribute to the spreading of pesticides in the environment. Although pesticide volatilisation is a known process, it has been scarcely measured, especially for periods beyond a few days after pesticide application. The reason is that pesticide concentration measurement, done mainly by offline gas chromatography-mass spectrometry, is challenging to deploy in the field for long-term studies. In this study, we report the first online concentration measurements of the fungicide chlorothalonil over a wheat field for several weeks after application, using a highly sensitive proton transfer reaction, quadrupole injection, time of flight, mass spectrometer (PTR-QI-TOF-MS). The main finding of this study is that chlorothalonil volatilisation, computed by inverse dispersion modelling, was sustained for more than three weeks after application. Overall, we evaluate that from 20 to 50% of the applied quantity of this fungicide may be lost by volatilisation to the atmosphere, which represents a quantity much higher than the currently accepted consensus. The analysis of the high-time resolution volatilisation dynamics further shows that volatilisation is the primary process of chlorothalonil dissipation over the 3 weeks, while penetration and photodegradation would be the dominant dissipation processes during the first 5 days. Our findings indicate that chlorothalonil gaseous volatilisation may be the most significant contributor to atmospheric exposure to this pesticide and its transfer to the environment. If we extrapolate our results to other volatile pesticides, we expect pesticide volatilisation to be a much larger exposure route than expected for humans and the environment.